2015
DOI: 10.4314/ahs.v15i1.1
|View full text |Cite
|
Sign up to set email alerts
|

High seropositivity of IgG and IgM antibodies against cytomegalovirus (CMV) among HIV-1 seropositive patients in Ilorin, Nigeria

Abstract: Background: Human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) is a major public health problem in sub-saharan Africa. Cytomegalovirus (CMV) has been reported to enhance HIV replication and accelerate the progression of HIV infection to AIDS. Objective: This study reports on the high seropositivity of immunoglobulin (Ig) G and M antibodies against CMV and the risk factors for CMV infection among HIV/AIDS patients in Ilorin, Nigeria. Method: A total of 180 consented HIV-1 seropositive pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
15
2
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 26 publications
(34 reference statements)
14
15
2
1
Order By: Relevance
“…Our study showed non-statistically significant higher prevalence rate of CMV IgM in the male than female subjects, which is similar to the observations of Ojide et al, (31) and Fowotade et al, (35) among their HIVinfected adults cohort. Musa et al, (22) however had a contrary observation in Kano where they reported more female patients living with HIV having significantly higher CMV IgM than their male counterparts (8.7% vs 4.3%, p<0.01) although no reason for such finding was proffered.…”
Section: Discussionsupporting
confidence: 92%
“…Our study showed non-statistically significant higher prevalence rate of CMV IgM in the male than female subjects, which is similar to the observations of Ojide et al, (31) and Fowotade et al, (35) among their HIVinfected adults cohort. Musa et al, (22) however had a contrary observation in Kano where they reported more female patients living with HIV having significantly higher CMV IgM than their male counterparts (8.7% vs 4.3%, p<0.01) although no reason for such finding was proffered.…”
Section: Discussionsupporting
confidence: 92%
“…This study reported that 10.4% of the HIV seropositive patients were anti-CMV IgM seropositive indicating current infection or reinfection/reactivation to cytomegalovirus. This is consistent with a previous study among HIV patients in Nigeria that found an 11.1% anti-CMV IgM seroprevalence [20]. In another study in Brazil, anti-CMV IgM seroprevalence of 11.36% among HIV infected prison inmates was reported [21].…”
Section: Discussionsupporting
confidence: 92%
“…This shows that CMV and HIV synergy to down regulate the immune system among the co infected participants. A similar observation was made in Nigeria [20]. All the patients who had no formal education had a 100% exposure to CMV indicating lack of awareness on basic risk factors and prevention mechanism due to lack of exposure to any form of education.…”
Section: Discussionsupporting
confidence: 71%
“…7 A taxa da infeção por CMV em indivíduos com VIH é muito elevada. Na Nigéria, segundo Fowotade et al, 8 é de 93,9 %. Em Moçambique, não existem dados estatísticos oficiais sobre a prevalência da infeção CMV em doentes com VIH.…”
Section: Discussionunclassified